The determinants of employee engagement: the study among academic staff in Malaysia private higher education institutions - Subhacini, Subramaniam (2021)
Employee engagement is crucial for the development of any organisation. Abundant studies have shown that organisations with engaged employees experience greater benefits. However, studies found that there is a crisis in terms of employee engagement among academic staff working in the private higher education sector and it needs to be addressed at the earliest to achieve the aspiration of the government to position the country as a hub for tertiary education in the region. Thus, using social exchange theory and job demand-resource (JD-R) model, this study was carried out to investigate the relationship between job demands (work-family conflict, work overload) and job resource factors (perceived organisational support, rewards and recognition) and employee engagement. The data was collected from 341 academic staff working in the selected private universities through an online survey and the respondents were selected based on disproportionate stratified random sampling method. SPSS version 23 was used to test the proposed hypotheses of the study. The results of the study indicated that job demand factor of work-family conflict negatively influenced employee engagement. However, the other job demand factor, which is work overload, did not reveal an anticipated negative relationship with employee engagement. The result also found that job resource factors (perceived organisational support, rewards and recognition) are positively related to employee engagement. This study contributes to the engagement literature by examining the factors affecting employee engagement among Malaysian academic staff, which has been carefully selected to suit the academics’ work setting and the nature of their job. Moreover, the study will also guide the practitioners to propose policies and strategies to enhance the engagement of academic staff.